Pengaruh Pembelajaran Ekonomi Islam Terhadap Minat Mahasiswa Menabung di Bank Syariah (Studi Pada Mahasiswa Ilmu Komunikasi UIN Sumatera Utara) - Muhammad Albahi (Keguruan, 2022)
There are two types of banks in Indonesia: conventional banks and Islamic banks. Efforts to develop Islamic banks must also be focused on the market or the community as service recipients (consumers) of financial institutions. They don't just focus on legal and regulatory considerations. This study intends to ascertain the impact of Islamic Economics education on banking students' interest in Islamic institutions, especially among students of communication sciences. UIN North Sumatra became the research location. Quantitative research methodology was applied. In this investigation, direct linear regression analysis was used. The data sources of this research combine primary and secondary sources. In this study, basic random sampling was used as the sample method. According to the Sig value of the ANOVA table. = 0.027, which indicates a significance level (0.05) or Ho is rejected, the regression equation Y = 14.186 + 0.289X is significant and linear, indicating that understanding Islamic banking has a positive impact on students' interest in saving in Islamic banks. This is especially true for Communication Studies students at UIN North Sumatra. The correlation between learning Islamic Economics and the interest in saving in Islamic banks shows that students' interest in saving in Islamic banks increases along with the increase in students' understanding of Islamic banks.